Biocatalytic synthesis of poly(ε‐caprolactone) using modified lipase in ionic liquid media. Issue 4 (21st March 2016) - Yuan, Jiugang; Dai, Yaping; Yu, Yuanyuan; Wang, Ping; Wang, Qiang; Fan, Xuerong
Abstract : Ionic liquids have been used as exceptional nonaqueous reaction media for enzymatic transformation. The ring‐opening polymerization of ε‐caprolactone catalyzed by Novozyme‐435 lipase was successfully conducted in 1‐butyl‐3‐methylimidazolium hexafluorophosphate ([Bmim]PF6 ) ionic liquid. 1 H‐NMR and MALDI‐TOF analyses of poly(ε‐caprolactone) (PCL) formed by Novozyme‐435 lipase‐catalyzed reaction revealed an asymmetric telechelic α‐hydroxy‐ω‐carboxylic acid end group. The effects of enzyme concentration, temperature, reaction time, and water activities on monomer conversion and Mn were systematically evaluated. Through the optimization of reaction conditions, PCL was produced in 85% monomer conversion, with an Mn of 5942, in [Bmim]PF6 at 60°C for 48 h. DSC results demonstrated that high‐molecular‐weight PCL exhibited an excellent thermal property. SEM results showed that PCL had a clear spherulites structure, which could provide a large surface area for cell adhesion. These results showed that [Bmim]PF6 ionic liquid was suitable for the biocatalytic synthesis of PCL using Novozyme‐435 lipase, and could be used as alternative environmentally friendly media to replace the traditional organic solvents.